2022
DOI: 10.1111/aji.13529
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical outcome of intrauterine administration of peripheral mononuclear cells or human chorionic gonadotropin in unexplained implantation failure

Abstract: Problem: Intrauterine administration of autologous peripheral blood mononuclear cells (PBMCs) or human chorionic gonadotropin (hCG) has been proposed to facilitate embryo implantation, while its effect on clinical outcome of women with previous implantation failure (RIF) in frozen/thawed embryo transfer (FET) cycles is still unclear. Method of study: A total 523 patients having not experienced successful clinical pregnancy were enrolled in our study, including 207 repeat implantation failure (RIF) patients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For instance, intrauterine injection of hCG has been suggested to increase endometrial Tregs in patients with Treg‐reduced repeat implantation failure (RIF) with concomitant improvement in pregnancy outcome 10 . However, another study showed that neither Intrauterine administration of hCG nor hCG‐activated PBMC can improve clinical outcomes for both RIF patients before frozen embryo transfer (FET) embryo transfer 11 …”
Section: Immunological Indicators For Predicting Pregnancy Failure An...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, intrauterine injection of hCG has been suggested to increase endometrial Tregs in patients with Treg‐reduced repeat implantation failure (RIF) with concomitant improvement in pregnancy outcome 10 . However, another study showed that neither Intrauterine administration of hCG nor hCG‐activated PBMC can improve clinical outcomes for both RIF patients before frozen embryo transfer (FET) embryo transfer 11 …”
Section: Immunological Indicators For Predicting Pregnancy Failure An...mentioning
confidence: 99%
“…10 However, another study showed that neither Intrauterine administration of hCG nor hCG-activated PBMC can improve clinical outcomes for both RIF patients before frozen embryo transfer (FET) embryo transfer. 11…”
Section: Immunological Indicators For Predicting Pregnancy Failure An...mentioning
confidence: 99%
“…100 However, controversies exist on the beneficial effect of LIT treatment in patients with RIF and recurrent pregnancy loss. [101][102][103][104] Thus, the roles of LIT in improving clinical outcomes in RIF need more systematic investigations.…”
Section: Immunotherapies In Rifmentioning
confidence: 99%
“…Mechanisms such as reduction in the Th1/Th2 ratios and their cytokines production, altered antipaternal cytotoxic antibodies, enhanced expression of progesterone‐induced blocking factor, anti‐idiotypic antibodies, and mixed lymphocyte reaction blocking antibodies are proposed to be involved in improving outcomes of LIT in RIF and recurrent pregnancy losses 100 . However, controversies exist on the beneficial effect of LIT treatment in patients with RIF and recurrent pregnancy loss 101–102,103–104 . Thus, the roles of LIT in improving clinical outcomes in RIF need more systematic investigations.…”
Section: Introductionmentioning
confidence: 99%
“…[ 38 ] 207 Human frozen/thawed embryo Cleavage and blastocyst HCG, 4 h No effect on implantation rate and live birth rate Mei et al. [ 150 ] RIF: recurrent implantation failure; PBMC: peripheral blood mononuclear cells; HCG: human chorionic gonadotrophin; CRH: corticotropin releasing hormone; HMG: human menopausal gonadotrophin. …”
Section: The Role Of Macrophages In Male Idiopathic Infertilitymentioning
confidence: 99%